Stereolithography (SLA) 3D printing for fabrication of microfluidic device - Chia, Zhi Kai (2018)
For the past decade, the concept of ‘Lab-on-a-chip’ has been getting increasingly popular with biomedical applications. They are used to describe microfluidic devices that are capable of performing laboratory functions, such as sample mixing and particles separation. Driven by the numerous advantages of handling samples at micrometer-scale, more and more researchers are starting to take interest in these devices. However, due to the fact that their fabrication processes are tedious and time consuming, microfluidic devices are still not commonly utilised in the relevant industries. In recent years, the field of 3D printing has grown rapidly. Being an efficient technology which is capable of manufacturing micrometre-sized structures, it has prompted researchers to introduce 3D printing as a method of fabrication for microfluidic devices. In this project, a study was conducted to investigate the ability of a stereolithography based 3D printer on fabricating micro-size structures for microfluidic devices. This report serves to provide a detailed recount of the procedures the author had taken in order to fabricate a micromixer, using the assigned 3D printer. It also describes the experiment set-up arranged by the author in order to evaluate the micromixer’s functionality and performance. Experiments were conducted for fluids flowing in the range of Reynolds number 0.2 to 200. Through analysis of the results, it was concluded that for all cases of individual Reynolds number within the stated range, fluids exiting the micromixer were significantly mixed. Amount of fluids mixed reached above 90% for most cases, while for a few exceptional ones, the amount of fluids mixed stays within the range of 70 to 80%. Nevertheless, the obtained results have proven that the fabricated micromixer is able to serve its function well, which verifies the potential of 3D printing in the field of microfluidics